Desktop-Stereolithography 3D Printing of a Polyporous Extracellular Matrix Bioink for Bone Defect Regeneration - Luo, Yunxiang; Pan, Hao; Jiang, Jiuzhou; Zhao, Chenchen; Zhang, Jianfeng; Chen, Pengfei; Lin, Xianfeng; Fan, Shunwu (Frontiers in Bioengineering and Biotechnology, 2020)
Decellularized tendon extracellular matrix (tECM) perfectly provides the natural environment and holds great potential for bone regeneration in Bone tissue engineering (BTE) area. However, its densifying fiber structure leads to reduced cell permeability. Our study aimed to combine tECM with polyethylene glycol diacrylate (PEGDA) to form a biological scaffold with appropriate porosity and strength using stereolithography (SLA) technology for bone defect repair. Methods: The tECM was produced and evaluated. Mesenchymal stem cell (MSC) was used to evaluate the biocompatibility of PEGDA/tECM bioink in vitro. Mineralization ability of the bioink was also evaluated in vitro. After preparing 3D printed polyporous PEGDA/tECM scaffolds (3D-pPES) via SLA, the calvarial defect generation capacity of 3D-pPES was assessed. Results: The tECM was obtained and the decellularized effect was confirmed. The tECM increased the swelling ratio and porosity of PEGDA bioink, both cellular proliferation and biomineralization in vitro of the bioink were significantly optimized. The 3D-pPES was fabricated. Compared to the control group, increased cell migration efficiency, up-regulation of osteogenic differentiation RNA level, and better calvarial defect repair in rat of the 3D-pPES group were observed. Conclusion: This study demonstrates that the 3D-pPES may be a promising strategy for bone defect treatment.